2021
DOI: 10.1136/neurintsurg-2021-017818
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of balloon-mounted stent in the treatment of symptomatic intracranial atherosclerotic disease: a multicenter experience

Abstract: BackgroundRandomized clinical trials have failed to prove that the safety and efficacy of endovascular treatment for symptomatic intracranial atherosclerotic disease (ICAD) is better than that of medical management. A recent study using a self-expandable stent showed acceptable lower rates of periprocedural complications.ObjectiveTo study the safety and efficacy of a balloon-mounted stent (BMS) in the treatment of symptomatic ICAD.MethodsProspectively maintained databases from 15 neuroendovascular centers betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…10,12,22,33 Furthermore, it has been described that rates of sICH does not seem to increase after acute stenting of the cervical intracranial internal carotid artery in patients with LVOS and tandem occlusions nor after intracranial stenting in those with ICAD who were treated within 24 hours of the qualifying event. 34–36 Interestingly, subgroup analysis showed lower odds of sICH in patients who received IV tPA (unadjusted OR, 0.84 [95% CI, 0.73–0.97]; P =0.03). While no significance was achieved, our results align with a previous study showing numerically lower rates of sICH in patients who received glycoprotein IIb/IIIa inhibitors and underwent RS after IV tPA administration than not (4.0% versus 5.1%, P =0.999).…”
Section: Discussionmentioning
confidence: 99%
“…10,12,22,33 Furthermore, it has been described that rates of sICH does not seem to increase after acute stenting of the cervical intracranial internal carotid artery in patients with LVOS and tandem occlusions nor after intracranial stenting in those with ICAD who were treated within 24 hours of the qualifying event. 34–36 Interestingly, subgroup analysis showed lower odds of sICH in patients who received IV tPA (unadjusted OR, 0.84 [95% CI, 0.73–0.97]; P =0.03). While no significance was achieved, our results align with a previous study showing numerically lower rates of sICH in patients who received glycoprotein IIb/IIIa inhibitors and underwent RS after IV tPA administration than not (4.0% versus 5.1%, P =0.999).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of balloon-mounted stents is the added radial force as compared in Neuro-Form atlas (Stryker Neurovascular) and the pre-balloon angioplasty associated with deployment; however, due to their stiffness, navigating such stents could be challenging, particularly in tortuous anatomy. Mohammaden et al recently evaluated the use of balloon-mounted stent in the treatment of symptomatic ICAS ( 46 ). Among 232 patients with symptomatic ICAS patients who failed medical management and were treated with balloon-mounted stents, 5.6% had strokes within 72 h, 3.9% were ischemic, and 1.7% were hemorrhagic.…”
Section: Discussionmentioning
confidence: 99%
“…However, even with aggressive medical treatment, symptomatic ICAS patients with severe stenosis are still at high risk of stroke. Thus, intervention is an important treatment alternative for these patients [ [5] , [6] , [7] ]. Some clinical studies have demonstrated the short-term efficacy of endovascular stenting in severe symptomatic ICAS patients, although its effecicacy is still controversial [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%